The Role of Baitul Maal Wa Tamwil in Enhancing MSME Empowerment in Lubuklinggau: A Case Study of BMT Al-Azhaar - Binbud Florado; Rachmiya Saputri; Muhammad saleh; Peny Cahaya Azwari (Yayasan Payungi Smart Madani, 2025)
This study aims to analyze the role, strategy, and obstacles of BMT Al-Azhaar in enhancing the empowerment of Micro, Small, and Medium Enterprises (MSMEs) in Lubuklinggau City. This research uses a qualitative method, with data collected through observation, interviews, and documentation analyzed through data reduction, display, verification, and conclusion drawing. The results show that BMT Al-Azhaar plays two key roles in empowering MSMEs: financing and coaching. The financing role distances the community from usury-based practices and provides equitable Sharia-compliant financial support. In contrast, the coaching role helps free MSMEs from dependence on loan sharks through business guidance and mentoring. The strategies used by BMT Al-Azhaar include community-based, local resource-based, and sustainability-based approaches. The institution faces internal obstacles—such as limited human resources and non-performing loans—and external challenges, including public misconceptions equating BMT with conventional financial institutions due to fixed margin perceptions. This study contributes to the literature on Islamic microfinance by presenting a contextual model of MSME empowerment that integrates Sharia-compliant financing with coaching rooted in local values and spiritual ethics. Its novelty is identifying BMT’s empathetic strategies, such as installment deferrals for disaster-affected clients and proactive public education to address misunderstandings about murabahah contracts. These findings affirm BMT Al-Azhaar’s role as a financial provider and an agent of Islamic economic literacy and holistic empowerment.